Surface integrity characterization based on time-delay of the magnetic Barkhausen noise voltage signal - Žerovnik, Pavle (Strojniški vestnik, 2014)
The captured magnetic Barkhausen noise (BN) signal is composed of a series of voltage impulses changes produced by movements of themagnetic domains. In most cases the captured voltage signals cannot be directly related to individual parameters to assess the material state,i.e. the properties, of the surface layer. For further efficient analysis of the voltage signals, an appropriate method for signal processing shouldbe chosen in order to use the characteristic value of the voltage signal.Our method of processing represents the time delay of a BN voltage signal, i.e. the maximum voltage value of the signal, with reference tothe sine wave of the magnetizing current. Measurement of the time delays of the voltage signals was carried out under optimum magnetizingconditions, which gave us the greatest number of voltage impulses in the signal. These are influenced by the turns and orientation of themagnetic domains.The aim of this research was to compare the voltage-signal time delay obtained with quenched and tempered specimens at twoneighbouring temperatures. The temperature differences ranged from T1= 10 °C, up to T2= 25 °C. These small temperature differences inthe tempering-temperature produced small differences in the micro hardness of the individual specimens and found out whether there weresignificant differences between micro hardnesses. The assessment of the reliability of the prediction of micro hardness was carried out usingthe Students t-test.
Keywords: Barkhausnov šum; časovna zakasnitev napetostnih signalov; mikromagnetna metoda; Studentov t-test; trdota; zanesljivost